Particle radiosurgery: a new frontier of physics in medicine - Bert, Christoph; Durante, Marco (Physica Medica, 2014)
Radiosurgery was introduced over half a century ago for treatment of intracranial lesions. In more recent years, stereotactic radiotherapy has rapidly advanced and is now commonly used for treatments of both cranial and extracranial lesions with high doses delivered in a few, down to a single fraction. The results of a workshop on Particle radiosurgery: A new frontier of physics in medicine held at Obergurgl, Austria during August 25-29 2013 are summarized in this issue with an overview presented in this paper. The focus was laid on particle radiosurgery but the content also includes current practice in x-ray radiosurgery and the overarching research in radiobiology and motion management for extracranial lesions. The results and discussions showed that especially research in radiobiology of high-dose charged-particles and motion management are necessary for the success of particle radiosurgery.
EVALuna2:18241